2002
DOI: 10.1007/s00402-001-0387-y
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous healing of acute anterior cruciate ligament (ACL) injuries - conservative treatment using an extension block soft brace without anterior stabilization

Abstract: To evaluate the spontaneous healing capability of acute anterior cruciate ligament (ACL) injuries, conservative treatment was applied in a selected group of 31 patients, who had low athletic demands. Each patient demonstrated a continuous ACL on magnetic resonance imaging (MRI), from the original femoral attachment through the tibial attachment, and an area of high intensity was detected in the substance of the ACL. The injured knees were treated using an extension block soft brace without anterior stabilizati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
55
0
4

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(59 citation statements)
references
References 16 publications
0
55
0
4
Order By: Relevance
“…However, several studies have reported a spontaneous healing of the ACL after acute rupture [4,6,8], and in most cases, the authors of these studies have indicated a nonoperative treatment with bracing and a specific rehabilitation program [4,6,8]. Thus, while most observers suggest a complete ACL rupture will not heal, there are apparently some situations in which it will heal.…”
Section: Introductionmentioning
confidence: 99%
“…However, several studies have reported a spontaneous healing of the ACL after acute rupture [4,6,8], and in most cases, the authors of these studies have indicated a nonoperative treatment with bracing and a specific rehabilitation program [4,6,8]. Thus, while most observers suggest a complete ACL rupture will not heal, there are apparently some situations in which it will heal.…”
Section: Introductionmentioning
confidence: 99%
“…Another possible explanation for the difference in PL bundle is that healing of a PL bundle with time may contribute to the more accurate rating of PL bundle integrity in the late MRI group. In fact, spontaneous healing of a torn ACL was demonstrated in several studies [2,8,11]. Nevertheless, further studies should be warranted to prove our speculation about the healing potential of the PL bundle.…”
Section: Discussionmentioning
confidence: 81%
“…Any high signal intensity due to edema or bleeding from acute mechanical injury would be expected to decrease as the acute responses resolve. [21][22][23] The unaltered signal intensity also does not support the theory that acute ligament injury invisible on MR images in the acute phase can cause the development of high signal intensity seen only at a later stage of injury, eg, after a repair process or due to accelerated degeneration. 11 We cannot completely rule out that such high signal intensity may occur later than 12 months after injury.…”
Section: Discussionmentioning
confidence: 89%